Neuroendocrine neoplasms of the thymus - Barone, Paul D.; Zhang, Chen (Frontiers in Immunology, 2024)
Neuroendocrine neoplasms of the thymus (tNENs), including typical carcinoid, atypical carcinoid, large cell neuroendocrine carcinoma, and small cell carcinoma, are rare tumors with scarce clinical and pathological data available in the literature. They share many common features with neuroendocrine neoplasms in other organs, such as those in the lungs, while demonstrating some distinct clinical and pathological features. This review aims to give an updated overview of each category of tNENs, focusing primarily on the pathologic diagnosis and differential diagnosis of these tumors.